Implementasi Program Boarding School Bilingual dalam menumbuhkan Maharah Kitabah Kelas VIII MTs Negeri 1 Purworejo - Ikmala Najwa Aulia; Firdaus; Ali Imron (Ta'bir Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Ilmu Kebahasaaraban, 2026)
This study aims to analyze the implementation of the Bilingual Boarding School program in developing mahārah kitābah (writing skills) for eighth-grade students at MTs Negeri 1 Purworejo. Mahārah kitābah is one of the essential skills in learning Arabic, requiring students to master vocabulary, sentence structure, writing rules, and the ability to express ideas coherently in written form. This research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The findings indicate that the Bilingual Boarding School program is implemented through the integration of madrasah-based formal education, pesantren systems, and foreign language learning within a residential environment. The program fosters the development of mahārah kitābah by increasing Arabic learning hours, promoting routine mufradat (vocabulary), muhadatsah (speaking exercises), Arabic debates, writing exercises, and the use of structured modules and digital learning media. Writing skills are developed gradually through dictation exercises (imla’), guided writing (kitabah muwajjahah), and short essay composition. Supporting factors include student motivation, peer support, teacher-student collaboration, structured learning modules, and adequate facilities. In contrast, inhibiting factors involve suboptimal daily use of Arabic, limited vocabulary, differences in initial student competence, technical issues, and a dense activity schedule. Evaluation is conducted through observation, oral and written tests, writing assignments, and direct correction (tashih). This study demonstrates that the Bilingual Boarding School program has the potential to serve as an effective model for Arabic language learning in a residential environment, particularly in enhancing students’ mahārah kitābah.